Adobe flash based learning media development in economic lessons - Muh. Fahrurrozi; Mohzana Mohzana (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
This study aims to determine the development of adobe flash-based audio-visual learning media in economic subjects, to determine the feasibility of adobe flash-based audiovisual learning media as a learning medium in the learning process, to determine student assessments in using adobe flash-based audiovisual learning media in subjects the economy. This media was tested in three stages, namely the individual trial stage, expert or expert test, material expert and media expert, small scale trial stage for 10 students, and large-scale or field trial stage for 26 students. Data collection techniques in this study used a questionnaire. The data obtained from the questionnaire were then analyzed descriptively quantitatively. The results showed several stages in this development, the quality of audiovisual learning media based on Adobe Flash based on the assessment of 1) material experts obtained a final average score of 85% including in the very feasible category, 2) media experts obtained a final average score of 88% included in the very feasible category, 3), small scale trials obtained a final average value of 91%, and 4) large scale / field trials obtained a final average value of 87% included in the very practical category. Based on the results of assessments from experts and students, it is very practical as a learning medium in the learning process.